Characterization of cp3 reveals a new bri1 allele, bri1-120, and the importance of the LRR domain of BRI1 mediating BR signaling - Shang, Yun (BioMed Central, 2011)
BACKGROUND: Since the identification of BRI1 (BRASSINOSTEROID-INSENSITIVE1), a brassinosteroids (BRs) receptor, most of the critical roles of BR in plant development have been assessed using various bri1 mutant alleles. The characterization of individual bri1 mutants has shown that both the extracellular and cytoplasmic domains of BRI1 are important to its proper functioning. Particularly, in the extracellular domain, regions near the 70-amino acid island are known to be critical to BR binding. In comparison, the exact function of the leucine rich-repeats (LRR) region located before the 70-amino acid island domain in the extracellular cellular portion of BRI1 has not yet been described, due to a lack of specific mutant alleles. RESULTS: Among the mutants showing altered growth patterns compared to wild type, we further characterized cp3, which displayed defective growth and reduced BR sensitivity. We sequenced the genomic DNA spanning BRI1 in the cp3 and found that cp3 has a point mutation in the region encoding the 13(th )LRR of BRI1, resulting in a change from serine to phenylalanine (S399F). We renamed it bri1-120. We also showed that overexpression of the wild type BRI1 protein rescued the phenotype of bri1-120. Using a GFP-tagged bri1-120 construct, we detected the bri1-120 protein in the plasma membrane, and showed that the phenotypic defects in the rosette leaves of bri1-301, a kinase-inactive weak allele of BRI1, can be restored by the overexpression of the bri1-120 proteins in bri1-301. We also produced bri1-301 mutants that were wild type in appearance by performing a genetic cross between bri1-301 and bri1-120 plants. CONCLUSIONS: We identified a new bri1 allele, bri1-120, whose mutation site has not yet been found or characterized. Our results indicated that the extracellular LRR regions before the 70-amino acid island domain of BRI1 are important for the appropriate cellular functioning of BRI1. Also, we confirmed that a successful interallelic complementation occurs between the extracellular domain mutant allele and the cytoplasmic kinase-inactive mutant allele of BRI1 in vivo.